Environmental monitoring and biomarkers of exposure to styrene in chemical industry - Fernandes, Daniela (2018)
ABSTRACT - Biomarkers of exposure to chemicals, such as styrene, allows to estimate the exposure to a particular compound by measuring the compound or it(s) metabolite(s) in body fluids. As an example, the determination of mandelic acid and phenylglyoxylic acid in urine. Indicators of genotoxicity are categorized as: (a) DNA and protein adducts; (b) DNA strand breaks. Styrene metabolism is initiated by Cytochrome P450 enzymes mediated by the oxidation of styrene to a reactive metabolite, the styrene-7,8-oxide. This study aims to review the environmental monitoring, complemented with biomarkers of exposure in order to understand its correlation and styrene genotoxicity. Systematic searches were performed to identify studies of occupational exposure to styrene and health effects in workers of chemical industries. To determine styrene air concentration, several studies used a personal air sampling method. A significant correlation has been found between styrene air concentration and mandelic and phenylglyoxylic acid concentration in urine. A significant relationship was found between individual levels of mandelic acid and phenylglyoxylic acid and styrene-7,8-oxide adducts to N-terminal valine in hemoglobin among exposed individuals. A strong correlation was also found between the frequency of DNA single-strand breaks, in mononuclear leukocytes, and styrene airborne level. The relationship between DNA damage, persistence and repair is complex, which complicates the relevance evaluation of potential genotoxic exposures difficult. There is conflicting evidence on the relationship between genotoxic response and exposure level. In future individual susceptibility studies, the individual genotypes associated with the metabolic route and DNA damage of styrene (metabolizing enzymes and DNA repair enzymes) should be analyzed. From the analysis of several studies it was found that indeed there is a strong correlation between the exposure levels and exposure biomarkers; however, no evidence was found regarding the styrene genotoxicity.